Representative 3D shape of the distal femur, modes of variation and relationship with abnormality of the trochlear region. (20th September 2019) - Cerveri, Pietro; Belfatto, Antonella; Manzotti, Alfonso
Abstract: The anatomy of the distal femur has a predominant influence on the mechanics of both patello- and tibio-femoral joints. Especially, the morphological degeneration of the trochlear region dramatically affects the overall knee biomechanics and, from a clinical point of view, the staging of such a degeneration is fundamental to tailor the optimal therapeutic solution. The description of morphological variability and pathological inter-subject differences of the trochlea can be achieved by means of statistical shape modeling of a set of three-dimensional surfaces. This representation encodes information, spread into the dataset, in terms of modes of variations that model global, regional and even local morphological features. In view of that, the aim of this study was to develop a statistical shape model of the distal femur to capture the variability of the trochlear region into specific modes of variation and to study the interplay between the variation of the trochlea and the condylar regions. Using CT scans of patients affected by different levels of abnormality of the trochlear region, the distal femur geometries were co-registered to a reference shape using the pair-wise correspondence approach and principal component analysis provided the key modes of variation (MoVs). Apart from the first two MoVs, which described the global magnitude of the femur and the shaft length, the main following ones showed high correlation with sulcus depth ( r 2 = 0.70 ), sulcus angle ( r 2 = 0.70 ), lateral trochlear inclination ( r 2 = 0.66 ), and height of the two condylar facets in the anterior direction ( r 2 = 0.66 ), whose abnormal variations are typical signs of trochlear degeneration. High interplay between trochlear abnormalities and notch width ( r 2 = 0.71 ), lateral condylar size ( r 2 = 0.67 ), and medial condylar size ( r 2 = 0.99 ) was found. Interestingly, the model predicted morphological associations not included in the training dataset, nonetheless difficult to demonstrate physiologically. Interestingly from a biomechanical point of view, the distribution of some MoVs was found statistically different across the patients featuring physiological and pathological ranges of hip-knee-ankle alignment, femoral internal-external rotation and tibial slope. However, no linear correlation was found between the angular indexes and such MoVs. As a result, we can assert that statistical modeling of the distal femur are to date an effective way to visualize and quantify abnormalities of the trochlear regions supporting the introduction of advanced analysis, diagnostic and treatment support tools to elucidate physiologic and pathological variability in the morphology, to drive the staging and assist the selection of the optimal treatment option tailored to the patient.